Mechanism of a Volatile Organic Compound (6-Methyl-2-Heptanone) Emitted From Bacillus subtilis ZD01 Against Alternaria solani in Potato - Zhang, Dai; Qiang, Ran; Zhao, Jing; Zhang, Jinglin; Cheng, Jianing; Zhao, Dongmei; Fan, Yaning; Yang, Zhihui; Zhu, Jiehua (Frontiers in Microbiology, 2022)
The antagonistic mechanisms of soluble non-volatile bioactive compounds, such as proteins and lipopeptides emitted from Bacillus, have been widely studied. However, there are limited studies on the antifungal mechanisms of volatile organic compounds (VOCs) produced by Bacillus against plant fungal diseases. In this study, the antagonistic mechanisms of one specific VOC, 6-methyl-2-heptanone, against Alternaria solani were investigated. To optimize the extraction conditions of headspace solid-phase microextraction, a 50/30-µm divinylbenzene/carboxen/polydimethylsiloxane fiber at 50°C for 40 min was used. For gas chromatography-mass spectrometry using a free fatty acid phase capillary column, 6-methyl-2-heptanone accounted for the highest content, at 22.27%, of the total VOCs from Bacillus subtilis ZD01, which inhibited A. solani mycelial growth strongly in vitro. Therefore, 6-methyl-2-heptanon was selected as the main active chemical to elucidate the action mechanisms against A. solani. Scanning and transmission electron microscopy analyses revealed that after exposure to an EC50 dose of 6-methyl-2-heptanone, A. solani hyphal cells had a wide range of abnormalities. 6-Methyl-2-heptanone also caused the capture of cellular fluorescent green label and the release of ATP from outer membranes A. solani cells, which may enhance 6-methyl-2-heptanone ability to reach the cytoplasmic membrane. In addition, 6-methyl-2-heptanone showed strong inhibitory effect on A. solani condial germination. It also damaged condial internal structures, with the treated group having collapsed shrunken small vesicles as observed by transmission electron microscopy. Because 6-methyl-2-heptanone showed strong effects on mycelial integrity and conidial structure, the expression levels of related pathogenic genes in A. solani treated with 6-methyl-2-heptanone were investigated. The qRT-PCR results showed that transcriptional expression levels of slt2 and wetA genes were strongly down-regulated after exposure to 6-methyl-2-heptanone. Finally, because identifying the functions of pathogenic genes will be important for the biological control of A. solani, the wetA gene was identified as a condia-associated gene that plays roles in regulating sporulation yield and conidial maturation. These findings provide further insights into the mechanisms of VOCs secreted by Bacillus against A. solani.